ISLAMIC SOCIAL REPORTING: THE DIFFERENCE OF PERCEPTION BETWEEN USER AND PREPARER OF ISLAMIC BANKING IN INDONESIA - Dhiona Ayu Nani (TECHNOBIZ : International Journal of Business, 2019)
Islamic banking has functions that are not merely oriented towards gaining profit but also related to social roles in society. Muhammad (2010) explain that financial report makers as part of companies tend to minimize reporting costs to ensure cost efficiency because their main goal is economic performance. On the other hand, users who represent the community expect Islamic banking to have social accountability because the existence of these companies is within the community. Therefore, the discussion about accountability of Islamic banking in the social field becomes interesting to be studied. This study aims to determine the perceptions of users and preparers of financial statements on the main objectives of Islamic banking social report, the motivation of Islamic banking to present social report, the potential groups of social report users and the information that must be disclosed on a social report. This study uses two types of respondents, namely the users represented by lecturers and students and the preparers represented by Islamic Bank employees in one of the big cities in Indonesia. The analytical method used is t-test and Multiple Response Analysis. The results of the study show that there are no differences in perceptions between the users and preparers of financial statements towards the main objectives of Islamic banking social report, the motivation of Islamic banking to present social report and potential users of Islamic banking social report. Meanwhile, there is the difference in perceptions between users and preparers of financial statements of information that must be disclosed in the Islamic banking social report.Keywords: Islamic Banking, Social Reporting in Islamic Perspective, Accountability.